Cone photoreceptors respond to their own glutamate release in the tiger salamander. - Picaud, S (1995)
Pulse-like currents resembling miniature postsynaptic currents were recorded in patch-clamped isolated cones from the tiger salamander retina. The events were absent in isolated cones without synaptic terminals. The frequency of events was increased by either raising the osmotic pressure or depolarizing the cell. It was decreased by the application of either glutamate or the glutamate-transport blockers dihydrokainate and D,L-threo-3-hydroxyaspartate. The events required external Na+ for which Li+ could not substitute. The reversal potential of these currents followed the equilibrium potential for Cl- when internal Cl- concentration was changed. Thus, these miniature currents appear to represent the presynaptic activation of the glutamate receptor with glutamate transporter-like pharmacology, caused by the photoreceptor's own vesicular glutamate release. Using a noninvasive method to preserve the intracellular Cl- concentration, we showed that glutamate elicits an outward current in isolated cones. Fluorescence of the membrane-permeable form of fura-2 was used to monitor Ca2+ entry at the cone terminal as a measure of membrane depolarization. The increase in intracellular Ca2+ concentration, elicited by puff application of 30 mM KCl, was completely suppressed in the presence of 100 microM glutamate. Puff application of glutamate alone had no measurable depolarizing effect. These results suggest that the equilibrium potential for Cl-, ECl, was more negative than the activation range for Ca2+ channels and that glutamate elicited an outward current, hyperpolarizing the cones.